Bifidobacterium fermentation with infant formulas is associated with benefits for gut and brain barrier function - Emily G. Knox; Paula Sánchez-Díaz; Colin Buttimer; Sarah-Jane Leigh; Klara Vlckova; Colin Hill; Elaine Kennedy; Jonathan O’Regan; Seamus McSweeney; David Goulding; Maria Rodriguez Aburto; Caitriona M. O’Driscoll; et al. (Journal of Functional Foods)
The gut and blood-brain barrier are essential components of the microbiota-gut-brain axis and are influenced by diet, particularly in infancy. Breast milk supports gut and brain barrier function, but infant formulas often lack key protective components. Bifidobacterium is the predominant bacteria in the infant gut microbiome. Here, we evaluated the impact of four infant formulas fermented with three Bifidobacterium strains, originally isolated from infant stool, on gut and BBB integrity. Cell-free supernatants from these fermentations were exposed to cultures of T84 colonocytes (gut barrier model) or bEnd.3 brain endothelial cells (BBB model), with and without lipopolysaccharide challenge. All three Bifidobacterium strains exhibited protective effects on both gut barrier and BBB integrity with a profile that depended on the infant formula. Taken together, this data indicates that the fermentation products of relevant Bifidobacterium strains with infant formulas may provide protection against barrier disruption.